A MATRIMONIAL AGENCY IN THE SECOND CONSTITUTIONAL PERIOD: THE OFFICE OF FACILITATING MARRIAGE AND FAMILY FORMATION - Yasar, Fatma Tunc (SELCUK UNIV, INST TURKISH STUDIES, 2020)
In the publications of the Second Constitutional period, there was an agenda that the Ottoman population has generally decreased, the age of first marriage has increased, the rate of marriage fell and the family structure began to deteriorate. This agenda played an important role in shaping the policies of Union and Progress government on population and family and marriage as a topic became a public matter to be discussed on. In 1911, Yusuf Cemil Bey established The Office of Facilitating Marriage and Family Formation to promote marriage and family establishment in Cemberlita, Istanbul. In its published program, the Office claimed that it is performing its national duty by referring to the incentive population and marriage promotion policies of the Union and Progress government and evaluated its initiative as a private enterprise, which is the achievement of the Second Constitutional era. Ottoman political authorities, on the other hand, described this institution, which they cannot define as a community (cemiyet), as a kind of commercial club. This article examines the establishment, status and working manner of the Office of Facilitating Marriage and Family Formation by focusing on the writings and documents issued by political authorities and the Program published by the Office to introduce itself to the audience. In this context, it claims that although the Office legitimized its establishment according to the policy of facilitating marriage to increase population, the Office operated as a commercial enterprise that turned the search for marriage into a market in the atmosphere of Second Constitutional period and thus introduced the Ottoman society to a new practice of seeking marriage.
Keywords: The Second Constitution; Family; Population; Marriage; Facilitating marriage; Arts & Humanities - Other Topics